2008
DOI: 10.1590/s0004-27302008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Associação das medidas antropométricas de localização de gordura central com os componentes da síndrome metabólica em uma amostra probabilística de adolescentes de escolas públicas

Abstract: Avaliou-se a associação entre medidas antropométricas de localização de gordura central: circunferências da cintura (CC) e abdominal (CA) e as razões cintura/quadril (RCQ) e cintura/estatura (RCE), independente do percentual de gordura corporal (%GC) e índice de massa corporal (IMC), com os componentes da síndrome metabólica (SM) em uma amostra probabilística de 610 (222 meninos e 388 meninas) adolescentes de 12 a 19 anos de escolas públicas de Niterói, RJ. Foram avaliados glicose e perfil lipídico pelo método… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
4
12
0
12
Order By: Relevance
“…The same association was observed in a study on adolescents 24 . These findings emphasize that excess weight contributes to central obesity, with a consequent increase in the risk of metabolic syndrome and cardiovascular mortality.…”
Section: Discussionsupporting
confidence: 86%
“…The same association was observed in a study on adolescents 24 . These findings emphasize that excess weight contributes to central obesity, with a consequent increase in the risk of metabolic syndrome and cardiovascular mortality.…”
Section: Discussionsupporting
confidence: 86%
“…When assessing the presence of MS components in accordance with the presence of insulin resistance, sex or age, it was observed that in the presence of IR, girls had a 2.9-fold higher risk than boys to have elevated TG and adolescents had 3 and 3.4-fold higher risk than children to have altered levels of TG and HDL-C. Insulin has several effects on lipid metabolism regulation, for instance, regulating the synthesis of triglycerides by adipocytes and participation IR enhances the oxidation of free fatty acids (FFA) in serum, provides substrate for the synthesis of TG in the liver and increases the hepatic release of TG-rich very low density lipoprotein (VLDL-c), to the serum, thereby increasing its levels 32 .…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, o mesmo não é observado em indivíduos obesos, devido às frequentes alterações que ocorrem na atuação de determinadas enzimas e no metabolismo lipídico em função da RI 4 . Esta, por sua vez, intensifica a oxidação dos AG livres no soro, fornece substrato para a síntese de TG no fígado e aumenta a liberação hepática de very low density lipoprotein, rica em TG, para o soro 23 .…”
Section: Tabela 2 -Variáveis Avaliadas Entre As Crianças Obesas E Eutunclassified